Raising Math Scores among Children in Low-Wealth Households: Potential Benefit of Children’s School Savings - Hamouda, O.F. (Journal of Income Distribution®, 2014)
Recent findings using traditional regression methods show that children’s school savings is associated with higher math scores. We build on this research by using hierarchical linear modeling (HLM). Moreover, we suggest children’s school savings may have a stronger association with children’s math scores than either household wealth or children’s savings that is not designated for school. We find children with school savings have higher math scores than those without school savings. Further, we find evidence that children’s school savings mediates the relationship between household wealth and math scores. Policy implications for children living in low-wealth households discussed.